Perancangan Kampanye Sosial Untuk Para Orang Tua Tentang Penanganan Tantrum Pada Anak Usia 3-5 Tahun Di Kota Batusangkar - Hamdi, Fakhrizal; Fernando, Ferry; Rajab, Junaidi (INSTITUT SENI INDONESIA PADANGPANJANG, 2024)
Tantrum is anger with rage due to the inability to express desires or needs in words. Tantrums most often occur in children aged 3-5 years, because at that age children are developing language skills. Tantrums are something that is common in children, in the city of Batusangkar there are still many parents who don't know what tantrums are, and there are those who think Tantrums are a symptom of a child with needs. Due to parents' lack of understanding about what tantrums are and how to handle tantrums that occur in children, a social campaign was designed for parents about how to handle tantrums that occur in children. This social campaign was carried out in the form of seminars held at schools. by inviting parents as the audience. The data collection methods used were observation, interviews, questionnaires and also literature study. The analysis method used is SWOT analysis and the target audience is parents with an age range of 25-45 years. After collecting this data, we continue with the brainstorming process, preparing verbal concepts and visual concepts for the media that will be designed. The results of this design are seminars as the main media and also pocket books, posters, X-Banners, social media accounts, and also merchandise as supporting media.